Understanding paid subscription news: Audience perspectives on Readers' experiences and challenges - Tunjung Senja Widuri (Universitas Ahmad Dahlan, 2026)
Economic disruption in the digital media industry has encouraged news organizations to adopt subscription-based schemes as a sustainability strategy; however, within an ecosystem dominated by advertising-driven platforms and algorithmic personalization, news consumers are increasingly exposed to declining journalistic quality, widespread misinformation, reduced information diversity, and the reinforcement of filter bubbles. Against this backdrop, this study aims to examine the consumption of subscription-based news in Indonesia by analyzing readers’ acceptance of this model and their capacity to address issues of information quality, misinformation, diversity of sources, and polarization. This research employs a phenomenological approach, collecting data through in-depth interviews with three participants from the millennial and Generation Z cohorts who had accessed paid news services in Indonesia, which were subsequently analyzed using descriptive qualitative techniques. The findings indicate that subscription schemes contribute to improved quality and depth of news consumption, as subscribers tend to be more selective and place greater value on journalistic standards, whereas non-subscribers rely more heavily on free sources that are often less comprehensive. Nevertheless, paid access also carries the potential to restrict information availability and narrow the range of perspectives encountered. This study finds no conclusive evidence that subscription-based consumption mitigates polarization or significantly reduces the filter bubble effect. Therefore, this research demonstrates that subscription-based journalism can enhance information quality and limit exposure to misinformation, yet simultaneously risks fostering information exclusivity, underscoring the need for news organizations to balance monetization strategies with broader commitments to accessibility, diversity, and informational inclusivity.